Applying a hybrid MCDM technique in warehouse management - Ajripour, Iman (Vezetéstudomány / Budapest Management Review, 2022)
The main goal of this study is to apply Multi-Criteria Decision Making (MCDM) in managing a warehouse. One of the elements that could impact organization performance is warehouse management. Surplus inventory imposes some ad- ditional costs on the organization, and inadequate inventory stops the operation of an organization. For managing and controlling warehouse inventories, the MCDM method is recommended in this study. The inventories are categorized ba- sed on multi-criteria instead of a single criterion in ABC. To specify the criteria’s weight, Best-Worst Method is used, and to reach the final score of spare parts, the Analytical Hierarchy Process, and Technique for Order of Preference by Similarity to Ideal Solution is applied. Some strategies for managing and controlling organizations’ warehouse is recommended.